Evolução do momentum angular estelar em sistemas binários na vizinhança solar - Alves, Brício Warney de Freitas (2024)
This research examines the influence of binarity on stellar rotation, focusing on F and G mainsequence stars. Based on a robust dataset from the Geneva-Copenhagen Survey (GCS), which includes rotational velocities, mass, age, and metallicity, we analyze the variation of projected rotational velocity on the Hertzsprung-Russell (HR) diagram for both single and binary stars. The assessment particularly focuses on regions above and below the Kraft break, recently suggested by Beyer e White (2024), which defines a critical point around 6450 K in temperature. Our results indicate that, regardless of binarity, stellar rotation tends to increase toward more massive stars on the HR diagram. Furthermore, we find a significant relationship between angular momentum (J) and stellar mass, with a noticeable discontinuity around 1.5 solar masses (M⊙). This behavior suggests that high-mass stars are more efficient at preserving the angular momentum acquired during their formation, whereas low-mass stars exhibit greater angular momentum loss over time. For low-mass stars (<1.5M⊙), the relationship between angular momentum and mass follows J ∝M6.36±0.22 for primary stars in binary systems, whereas for single stars, this relationship is J ∝ M7.46±0.15. In high-mass stars, the results indicate J ∝ M2.33±0.80 for single stars and J ∝ M2.93±0.90 for binary stars. These findings confirm that more massive stars retain significantly more angular momentum throughout their evolution, while lower-mass stars experience a greater loss of angular momentum. Additionally, we analyze the rotational evolution of F and G-type stars in both binary and single contexts. The results show that binary stars experience a more pronounced rotational loss over time compared to single stars, highlighting the influence of tidal effects on the deceleration of their rotation.